Bases metodológicas para la implementación de sistemas de monitoreo de salud estructural de puentes en Perú - Huamancusi Huamaní, Karen Elena (2024)
Bridges are critical assets of a road network and also generate economic development for a country. The most probable cause of structural damage is durability, but the existence of natural phenomena and human influence cause an increase in severe damage leading to possible collapse. Currently, the traditional approach to infrastructure monitoring in Peru has led to inaccurate results that affect decision making for adequate bridge maintenance. On the other hand, Bridge Health Monitoring (BHM) shows a progressive technological advance worldwide, without leaving aside its own purpose of analyzing and determining structural integrity. For this reason, the present research establishes the methodological bases of BHM applied to the Peruvian reality. For the realization of this study, two items were framed: (i) Details of historical data collection based on bridge typology, constituted material, geographical condition, damage factors and environmental parameters. (ii) Details of technological monitoring where the BHM is implemented by compiling international guidelines and research on types of instrumentation and positioning of monitoring devices, data collection and processing, damage identification methods, calibrations and application of Artificial Intelligence (AI) from the location of sensors to the decision-making process of possible solutions. From both sections, guidelines are proposed to apply the BHM through a work plan that is in accordance with international standards in monitoring and AI. In conclusion, these guidelines serve as a guide of specifications for decision making for future bridge monitoring in Peru.